Penatalaksanaan Holistik pada Pasien Anak Usia 7 Tahun dengan Herpes Zoster melalui Pendekatan Kedokteran Keluarga di Puskesmas Rawat Inap Panjang - Harahap, Rara Julia Timbara; Nusadewiarti, Azelia (CV. Jasa Sukses Abadi, 2024)
Herpes zoster (HZ) is an acute vesicular eruption caused by reactivation of latent varicella-zoster virus (VVZ) in sensory ganglia previously exposed to primary varicella infection. The incidence of HZ increases with age but many case reports show that herpes zoster can also occur in adolescents and even in children. The purpose of this case report is to implement a holistic and comprehensive family doctor service by identifying risk factors, clinical problems, and patient management based on evidence-based medicine with a patient-centered and family approach. This study is a case report study. Primary data were obtained through history taking (autoanamnesis from the patient and alloanamnesis from the patient's family), physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. Patient Ms. K, 7 years old, has been diagnosed with uncomplicated herpes zoster, has concerns about his health condition, the patient feels inferior and is afraid that the disease cannot be cured and is afraid of transmitting it to other family members. The patient hopes that the complaints disappear completely and do not recur, so they can be comfortable with their activities as usual. The patient's limited knowledge of the illness and an unfavorable lifestyle are factors that cause problems that occur in patients and their families. The diagnosis of herpes zoster, in this case, was in accordance with several theories and a critical review of recent studies. Management has been given in accordance with the management guidelines. There is good progress in patients starting from decreased clinical symptoms to changes in behavior after an intervention based on evidence-based medicine that is family-approach and patient-centered.